Theoretical Prediction of ZnO Nanoporous Allotropes with Triangular Hollow - Tuoc, Vu Ngoc; Thao, Nguyen Thi (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: The advancement of technology has now made to enable not only growth materials in layer-by-layer or even in sub-layer with a desired ingredient. Further, it is expected to enable to manipulate on material layers at the desired address. This opens up opportunities for creating porous structures with specific allotropes - the purpose of materials engineering geometry. Zinc oxide (ZnO) material, along with wurtzite and zinblende, has been found in a large number of allotropes with substantially different properties, and hence, applications. Therefore, predicting and synthesizing new classes of ZnO allotropes is of great significance and has been gaining considerable interest. Herein, we perform a density functional theory based study, predicting several new series of ZnO hollow structures using the engineering geometry approach. The geometry of the building blocks allows for obtaining a variety of triangular, low-density nanoporous, and flexible hollow structures. We discuss their stability by means of the free energy computed within the lattice-dynamics approach. We show that all the reported structures are wide band gap semiconductors. Their electronic band structures are finally examined in detail. Keywords:  Nanoporous, Density Functional Theory (DFT), semiconductor.